Gaya Kepemimpinan Servant Leadership pada Perguruan Tinggi - Rohmah, Fitri Nur; Sayuti, Akhmad Fauzi (International Conference on Islamic Studies, 2021)
Leadership is a very vital factor in the world of education. In addition, until now leadership is still seen as a very important factor for organizational effectiveness, also affecting almost all human life. Higher education has distinctive characteristics that require certain leadership. Higher education in Indonesia is currently actively making changes, so its leaders must be able to make successful changes. Facing change requires leaders who are able to bring the college to speed up, even bolt to adapt to existing changes. Therefore, an ideal leadership model is needed. Servant leadership can be used as one of the references to achieve this. The characteristics of servant leadership is leadership that is able to listen to others, able to empathize, able to do healing, have awareness, able to make persuasion, able to make concepts, have a vision, able to perform service stylists, have a commitment to human growth, and able to build community. This research aims to present a theoretical framework and review of servant leadership with systematic literary review (SLR) methods. The results of the analysis showed that servant leadership could be used as an alternative model of leadership in college. Keywords: , .